2015
DOI: 10.1378/chest.14-2114
|View full text |Cite
|
Sign up to set email alerts
|

Exercise End-Tidal CO 2 Predicts Central Sleep Apnea in Patients With Heart Failure

Abstract: BACKGROUND:Increased CO 2 chemosensitivity and augmented exercise ventilation are characteristic of patients with heart failure (HF) with central sleep apnea (CSA). Th e aim of this study was to test the hypothesis that decreased end-tidal CO 2 by cardiopulmonary exercise testing predicts CSA in patients with HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
2
11
0
2
Order By: Relevance
“…In our study, _ VE/ _ VCO 2 slope correlated with peak exercise PETCO 2 (rho ¼ À0.79; p < 0.01) and also with resting PETCO 2 (rho ¼ À0.59; p < 0.01), a finding suggesting that the mechanisms underlying elevated _ VE/ _ VCO 2 and decreased PETCO 2 may not be limited to exercise and may also be present at rest. This concept is supported by other studies showing that patients with high _ VE/ _ VCO 2 and low PETCO 2 at peak exercise had increased _ VE/ _ VCO 2 and low PETCO 2 at rest [6,7]. Therefore, the common underlying mechanisms of _ VE/ _ VCO 2 and PETCO 2 may explain the PETCO 2 association with pulmonary complications and may justify its use as a prognostic marker for perioperative risk assessment.…”
Section: Commentsupporting
confidence: 58%
See 1 more Smart Citation
“…In our study, _ VE/ _ VCO 2 slope correlated with peak exercise PETCO 2 (rho ¼ À0.79; p < 0.01) and also with resting PETCO 2 (rho ¼ À0.59; p < 0.01), a finding suggesting that the mechanisms underlying elevated _ VE/ _ VCO 2 and decreased PETCO 2 may not be limited to exercise and may also be present at rest. This concept is supported by other studies showing that patients with high _ VE/ _ VCO 2 and low PETCO 2 at peak exercise had increased _ VE/ _ VCO 2 and low PETCO 2 at rest [6,7]. Therefore, the common underlying mechanisms of _ VE/ _ VCO 2 and PETCO 2 may explain the PETCO 2 association with pulmonary complications and may justify its use as a prognostic marker for perioperative risk assessment.…”
Section: Commentsupporting
confidence: 58%
“…Underlying mechanisms that alter _ VE/ _ VCO 2 seem to operate during exercise as well as at rest. Indeed, patients with an increased _ VE/ _ VCO 2 ratio and a low partial pressure of end-tidal CO 2 (PETCO 2 ) during peak exercise have been shown to have an increased _ VE/ _ VCO 2 ratio and a low PETCO 2 at rest also [6,7], a finding suggesting that resting ventilatory measurements may have value for risk prediction. Identification of a simple, easy to obtain resting ventilatory measurements that effectively predicts respiratory complications and death after thoracotomy may be useful because many patients are not able or are unwilling to perform CPET [8].…”
mentioning
confidence: 99%
“…P ET CO 2 may be decreased by hyperventilation and by increased dead space ventilation, i.e., by the same factors which determine V E /VCO 2 6 , suggesting the parameters are closely related 61 . In our previous studies we have shown HF patients with low P ET CO 2 and increased V E /VCO 2 at peak exercise also exhibit low P ET CO 2 and increased V E /VCO 2 at rest 7,66 suggesting factors which promote high V E /VCO 2 and low P ET CO 2 may not be limited to exercise.…”
Section: Ventilatory Control In Hfmentioning
confidence: 91%
“…Ventilatory control is frequently abnormal in patients with advanced HF and manifests as hyperventilation at rest 5 , during exercise 6 and with sleep 7 . The presence of hyperventilation has been associated with decreased functional capacity 6 , more severe symptoms 42 and increased mortality 43 in HF patients.…”
Section: Ventilatory Control In Hfmentioning
confidence: 99%
See 1 more Smart Citation